AS ESCOLAS TÉCNICAS DA REGIÃO METROPOLITANA DE PORTO ALEGRE-RS E A EXCELÊNCIA EM GESTÃO DA QUALIDADE - Freiesleben, Fernando Bittencourt (Revista Liberato, 2013)
This work aims to verify if the technical schools around Porto Alegre adopt administrative practices in relation to Excellence Criteria concerning the National Quality Award and, from this, to present a Management System Proposal. The research was started through a questionnaire making questions about the aspects of PNQ Criteria and school organization aspects. Was identified the points to be improved and it was possible to develop a Management Proposal according to the Criteria for a Good Performance, as away to put the schools in an initial stage of Quality in the search for the Excellence in Institutional Performance.